Subitizing in congenitally blind adults - Ferrand, Ludovic; Riggs, Kevin J.; Castronovo, Julie (Psychonomic Bulletin & Review, 2010)
We investigated the role of vision in tactile enumeration within and outside the subitizing range. Congenitally blind and sighted (blindfolded) participants were asked to enumerate quickly and accurately the number of fingers stimulated. Both groups of participants enumerated one to three fingers quickly and accurately but were much slower and less accurate with four to nine fingers. Within the subitizing range, blind participants performed no differently from both sighted (blindfolded) and sighted-seeing participants. Outside of the subitizing range, blind and sighted-seeing participants showed better performance than did sighted-blindfolded participants, suggesting that lack of access to the predominant sensory modality does affect performance. Together, these findings further support the claim that subitizing is a general perceptual mechanism and demonstrate that vision is not necessary for the development of the subitizing mechanism. © 2010 The Psychonomic Society, Inc.
Keywords: Experimental and Cognitive Psychology; Arts and Humanities (miscellaneous); Developmental and Educational Psychology